From Kontrollverlust to Kontrollgewinn: Rediscovering a Meso-Level Normative Hierarchy for Integrated Water Management in England Using On-Line Activities - Tkachenko, Nataliya; Procter, Rob; Jarvis, Stephen (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
This paper presents a unique study into how to identify a meso-level normative (i.e., institutional) hierarchy of procedures that aim to deliver the ecological status of waterbodies in the UK. Using traditional survey and workshop methods, the majority of recent studies concentrate on engagement practices between macro- (government bodies) and micro- (local residents) level structures, which can be potentially replicated elsewhere. Meso-level elements (middle-level structures of control) are often regarded as ‘subjective institutional change’, e.g., failures to implement programs locally or misinterpretations of reflexive dialogs with communities. Nevertheless, it is often only meso-level structures that are capable of promoting and replicating policies elsewhere. At the same time, there is increasing appeal by governmental departments for communities to ‘self-organize’ and take responsibility for prioritizing environmental tasks, which themselves might be instigated by local trusts and voluntary organizations, the existence of which remains largely unaccounted for by central offices. The recent proliferation of Twitter accounts, with the prominent themes of water, ecology and ecosystems, which include people, organizations, businesses and ‘bots’ of various types, presents new opportunities for digital methods to gain insights into structures and functions of these virtual communities. We hypothesize that our methods can produce invaluable insights into the ‘crafting’ of environmental institutions through approaches commonly ignored by traditional ‘analog’ meso-level mechanisms. We use the example of Integrated Catchment Management in the UK, and specifically the Tamar Catchment in southwest England, in order to demonstrate how well Twitter can capture this transitory meso-level environmental political system.